A tipping point of spreading viruses: Estimating the risk of household contact transmission of COVID-19 - Kurahashi, Setsuya; Mukai, Taisei; Sekine, Yukari; Nakajima, Keisuke; Otake, Keiko; Sugiyama, Junichi; Takizawa, Takeshi; Kakizawa, Yasushi (Frontiers in Physics, 2023)
This paper proposes a model that visualizes the risk of contact infection to family members when going outspreads to various items at home. Behavior data after returning home are extracted from the behavior survey, such as location and contact objects. The data tables are created, including a behavior history table, behavior probability table, contact probability table, number of visits table, contact circulation table, etc. The material transmission rate table is created by measuring the virus transmission rate after contact with droplets in a virus experiment laboratory. In the experiment, the synthetic agent created from the acquired data probabilistically performs movement and contact behavior after returning home and reproduces the state in which the virus attached to the hand or belongings, when going out, propagates to objects at home. Next, we examined the risk of a second family member returning home. As a result, virus-attached contacts within around 30 minutes after returning home were widely confirmed around the entrance and kitchen, suggesting the effectiveness of early hand-washing behavior. And the experiment showed that even if the first person returning home disinfected their hands inside the entrance, the virus remained in a part of the entrance, and the virus was spread inside the room by the second person returning home.